Heterometallic [Cu2Ln3] (Ln = DyIII, GdIII and HoIII) and [Cu4Ln2] (Ln = DyIII and HoIII) Compounds: Synthesis, Structure, and Magnetism. Issue 8 (23rd January 2017) - Biswas, Sourav; Bag, Prasenjit; Das, Sourav; Kundu, Subrata; van Leusen, Jan; Kögerler, Paul; Chandrasekhar, Vadapalli
Abstract : The syntheses, structures, and magnetic properties of the penta‐ and hexanuclear 3d/4f complexes [Ln3 Cu2 (LH)4 (MeOH)]ClO4 [Ln = Dy III (1 ), Gd III (2 ), and Ho III (3 )] and [Ln2 Cu4 (LH)4 ](ClO4 )2 [Ln = Dy III (4 ) and Ho III (5 )] are reported. These complexes are assembled from the ligand 2, 2′‐{2‐hydroxy‐3‐[(2‐hydroxyphenylimino)methyl]‐5‐methylbenzylazanediyl}diethanol (LH4 ); four triply deprotonated ligands are involved in the formation of these complexes. In spite of the different nuclearities, some structural features are common. In both of the families, the metal ions are connected to each other by two bridging oxygen atoms, which emanate from either an ethoxide group or a phenolate group of [LH] 3– . Detailed magnetochemical analyses of1 –5 indicate that1 and5 display temperature‐dependent out‐of‐phase signals up to 12 K in the absence of a direct‐current (dc) field; therefore, these compounds are single‐molecule magnets. Abstract : The sequential reactions of a Schiff base ligand (LH4 ) with Cu(ClO4 )2 · 6H2 O and Ln(NO3 )3 · 6H2 O afford the heteropentametallic compounds [Ln3 Cu2 (LH)4 (MeOH)]ClO4 (Ln = Dy III, Gd III, and Ho III ). A subtle change to the reaction conditions furnishes the heterohexametallic compounds [Ln2 Cu4 (LH)4 ][ClO4 ]2 (Ln = Dy III and Ho III ). The Dy III compounds exhibit single‐molecule magnetism.